Modal Testing of Rotors with Fluid Interaction - Agnes Muszynska (International Journal of Rotating Machinery)
Modal testing of rotating structures has specific aspects, and it requires a specialized approach. Classical modal testing when applied to active (rotating) structures does not provide complete results. These aspects, and specific application of sweep frequency circular input force perturbation testing of rotors rotating in fluid environment, are discussed in this paper.